2009
DOI: 10.4049/jimmunol.182.1.171
|View full text |Cite
|
Sign up to set email alerts
|

CCR5 Expression Levels Influence NFAT Translocation, IL-2 Production, and Subsequent Signaling Events during T Lymphocyte Activation

Abstract: Ligands of CCR5, the major coreceptor of HIV-1, costimulate T lymphocyte activation. However, the full impact of CCR5 expression on T cell responses remains unknown. Here, we show that compared with CCR5 ؉/؉ , T cells from CCR5 ؊/؊ mice secrete lower amounts of IL-2, and a similar phenotype is observed in humans who lack CCR5 expression (CCR5-⌬32/⌬32 homozygotes) as well as after Ab-mediated blockade of CCR5 in human T cells genetically intact for CCR5 expression. Conversely, overexpression of CCR5 in human T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
5

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 91 publications
2
60
0
5
Order By: Relevance
“…As for CCR5 and it ligands, it has been shown that CCL5, via CCR5, is required for effective activation of CCR5, thus serving as costimulatory signals in T cell activation (20), and that this interaction signals via NFAT translocation leading to IL-2 production by CD4 + T cells (22). Our results showing that all three CCR5 ligands may intercompensate one another to effectively induce this signal, and thus, only concurrent targeted neutralization of all of them would inhibit CD4 + T cell proliferation (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for CCR5 and it ligands, it has been shown that CCL5, via CCR5, is required for effective activation of CCR5, thus serving as costimulatory signals in T cell activation (20), and that this interaction signals via NFAT translocation leading to IL-2 production by CD4 + T cells (22). Our results showing that all three CCR5 ligands may intercompensate one another to effectively induce this signal, and thus, only concurrent targeted neutralization of all of them would inhibit CD4 + T cell proliferation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Contento et al (21) showed that during T cell activation by APCs, the chemokine receptors CCR5 and CXCR4 are recruited into the immunological synapse, where they deliver costimulatory signals mediated by their hetro-oligomerization. Very recently, Camargo et al (22) showed that the interaction between CCR5 and its ligands induces signals via NFAT translocation, leading to IL-2 production by CD4 + T cells, and that IL-2 production is highly related to CCR5 expression. The in vivo implications of these findings have never been explored.…”
mentioning
confidence: 99%
“…Like TNF-α, CCL5 is produced by a wide variety of cells including macrophages in response to M. tuberculosis infection [25]. In addition to its chemotactic property attracting a number of immune cells including T cells and macrophages, CCL5 directly contributes to T-cell activation [26][27][28]. Thus, significantly abated CCL5 production in mLNs is likely to preclude T-cell priming and proliferation in LPLA 2 KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…As the main HIV-1 coreceptor, C-C chemokine receptor type 5 (CCR5) is now recognized as a co-activation molecule at the surface of CD4 ϩ T cells, 62 it could be involved in immune activation and thereby in the rise in CD4 count. This could explain why the administration of a CCR5 antagonist resulted in a decrease in T-cell activation.…”
Section: Immune Activationmentioning
confidence: 99%